TUNJANGAN KINERJA DAERAH (TKD) DAN UPAYA PENINGKATAN KINERJA PEGAWAI - Wahyudi Kumorotomo (Badan Kepegawaian Negara | The National Civil Service Agency, 2011)
As a part of the grand design for administrative reform, the Indonesian government has initiatedtoincreasesalaries for public officials under the so-called remunerasi policy. This policy is aimed at changing the system in whichsalary and allowance for public servants was generally based on conventional principle of pay as entitlement rather than pay-forperformance. In order toboost the performance of public servants, Indonesia couldlearn from international practice, especially how to link salary and allowance with objective performance. The currently implemented remunerasi policy appeared to be lacking on relating the pay with performance indicators while there have been bureaucratic politics that hinder its ultimate goals. After decentralization, thereare new initiatives of pay-for-performance system under the TKD allowance. If they are implemented appropriately, this will help for a better prospect for improving public service performance in the future. However, it is fundamental that the TKD systems that are now being replicated in many Indonesian provinces and districts are directlyl inked to quantitative and stablei ndicators of performance. The two cases of Gorontalo and Jakarta provinces show that pay-for-performance system would be successful if the government initially set upviable performance indicators. Although the Gorontalo started with attendance as key indicators, it has been able to expand them to more objective performance indexes. On the other hand, the Jakarta provincial government are still using TKD based on structural positions rather than functional positions, some thing that may turn out to be less significant to improve public services. For most sub-national governments in Indonesia, there is still a big challenge of creating transparent, objective, quantifiable performance indicators. Key Words: allowance, performance, Civil Servants